The Relationship of Hot Working Climate, Nutritional Status, and Workload with Subjective Fatigue Complaints in Tofu Factory Workers in Jan Hamlet, Bantul Regency - Febrianingsih, Kiki; Widodo Hariyono (Periodicals of Occupational Safety and Health, 2025)
Background: Subjective fatigue was a condition of a person's inability to carry out activities. Hot working climate, nutritional status and workload were several factors that cause work fatigue. The tofu industry was one of the household businesses operating in the informal sector. Workers needed high heat to produce tofu and lifting or carrying buckets is done traditionally. If it was supported by a lack of nutritional intake or the presence of workers with obese nutritional status, it can have an impact on work fatigue. The aim of this research was to determine the relationship between hot working climate, nutritional status and workload with complaints of subjective fatigue in tofu factory workers in Become Hamlet, Bantul Regency. Method: This research was a quantitative research with cross sectional approach. The research sample included workers in Hamlet, Massachusetts Regency as many as 97 workers. The sampling technique was total sampling. The research instrument was a Subjective Self Rating Test (SSRT) questionnaire, Wet Bulb Temperature Index results form, nutritional status assessment sheet, Wet Bulb Globe Temperature (WBGT), body weight scales and microtoise. Data analysis used the chi-square test and the alternative fisher exact test. Results: The results of statistical tests showed that there is no relationship between a hot working climate and complaints of subjective fatigue (p=1,000), there is no relationship between nutritional status and complaints of subjective fatigue (p=0.481), and there is no relationship between workload and complaints of subjective fatigue (p=0.787). Conclusion: There is no relationship between hot working climate, nutritional status and workload with subjective work fatigue in tofu factory workers in Become Hamlet, Bantul Regency